THE ALTERNATIVE ELECTION OF ENHANCING THE EFFICIENCY OF BATIK PRODUCTION WRITING PRING SEDAPUR - Apriliana, Indah; Wahyudi, Agung (Inscientech: Journal of Industrial, Science and Technology, 2017)
The excessive use of resources leads to increase the production costs and wasted materials. It also resulted in a decrease in the level of the companyâs production efficiency. However, it is not easy to identify the problem of waste. Small batik industry in Magetan city which is famous for Batik Tulis Pring Sedapur pattern is also one of the businesses which are until now still looking for the inefficiency of the production process so that the daily output is less than optimal. Therefore, the interviews are conducted repeatedly to the expert to identify the causeâs problem of the daily output unpredictability. The result of these interviews will be an input to be used for data processing of AHP model. The criteria for the decision-making to choose the alternatives include time, cost, and output. While the proposed alternative is the addition of the labour pattern and the manufacture of the clothesline. The result of qualitative and quantitative data processing and consistency test show that the procurement of the clothesline can increase the efficiency of space and daily output. Keywords: Problem identification, efficiency, Delphi Method, AHP, Alternative choosing.